Alpha Enterprise : Nutritionfridge / Nurzahirah Mohd Yussof - Mohd Yussof, Nurzahirah (2020)
NutritionFridge is a fridge which provides systems that have information about nutrition. A new concept of this smart fridge is introduced which will allow healthier nutrition practices and improve health. It is intended for people who practice a healthy and balanced diet in their everyday life. This product's design and functionality are the friendly control panel and easy to handle. The unique features are this smart fridge will perform acts such as dietary control, nutrition monitoring, and eating habit analysis. The target market for this product is the household that comes from high-income level, especially for the age of 25 to 55. This is because in this range of age the income of the people is mostly in stable condition. Furthermore, the coverage for the target market only in three states of the urban area in Malaysia which are Kuala Lumpur, Putrajaya, and Selangor. These states our focusing because the population of households in high- income level is higher than the population of other states. The projections of Alpha Enterprise within 3 years also had been predicted in this study.